African food insecurity in a changing climate: The roles of science and policy - Onyutha1, Charles (Food and Energy Security, 2019)
African population is projected to double to 2.48 billion people by 2050. The population increase poses a serious challenge of increasing food supply to meet the future demand. This challenge is compounded by climate change impacts on agriculture. In this paper, how poverty contributes to household food insecurity is explored and measures suggested to help address this challenge. To plan adaptation measures, linkages among food insecurity, poverty, and illiteracy should be considered. For the sub-Saharan Africa (SSA), adaptation (focused on poverty alleviation) should be prioritized and preferred to mitigation. Enhancement of adaptive capacity should not only be tailored toward empowerment of women but also made highly localized to household levels. Generally, efforts could be geared toward yield gap closure, addressing challenges regarding food distribution, promoting non-farm income-generating activities, and unification of government priorities in agriculture and food security. Government in each country of the SSA should ensure that governance strongly embraces transparency, accountability, and integrity otherwise as it is said a fish rots from the head down. Estimates of uncertainty in predicting future climate and their implications on expenditure related to adaptation should to always be made in an integrated way and reported to support actionable policies. To increase credibility in climate prediction especially at local scales, advances toward improving climate models (for instance by refining spatiotemporal scales, enhancing models’ capacity to reproduce observed natural variability in key climatological variables like rainfall) should be made, and this requires support from the investment in climate science. Science–policy interfacing is required in planning and implementation of measures for adapting to climate change impacts. In summary, food insecurity and persistent poverty especially in the SSA should be of direct relevance and concern at a global scale. Thus, global collaboration in science is key to achieve food security in the SSA.
Keywords: Climate change; Food insecurity; Poverty; Science–policy interface; Sub-Saharan Africa (SSA)